Developing Bikan Waterfall geotourism through community-based tourism (CBT): Empowerment of the local tourism awareness group - Marlina A, Riam; Anaperta, Yoszi Mingsi; Aditya, Fariz; Heriawan, Rangga Agung Pribadi; Deni, Andri Van; Jesicel, William (Universitas Muhammadiyah Magelang, 2025)
Bikan Waterfall within the Rantih Geosite, Sawahlunto, possesses significant geological value from the Tertiary Ombilin Formation, offering high scientific and educational potential. However, its development is hindered by limited community capacity and a lack of geological interpretation facilities. This community service program aims to strengthen the capacity of the local Tourism Awareness Group (Pokdarwis) through a Community-Based Tourism (CBT) approach. The methodology involves participatory observation, educational geotourism socialization, environmental conservation actions, and the installation of geological interpretive signboards. The results demonstrate a significant increase in community geotourism literacy, the formulation of a CBT-based management strategy, and the availability of interpretive facilities that enhance the site's educational function. This initiative proves that the synergy between geological conservation and local participation effectively increases the competitiveness of Bikan Waterfall as a sustainable geotourism destination.